Efficacy of sewage sludge derived biochar on enhancing soil health and crop productivity in strongly acidic soil - Junior, Antonio; Guo, Mingxin (Frontiers in Soil Science, 2023)
Amending soils with sewage sludge-biochar is a promising waste management approach to reuse the waste while minimizing environmental contamination risks. Potting experiments were conducted to examine the efficacy of sludge-biochar amendments on enhancing soil health and crop productivity. Strongly acidic soil (pH=5.0) was amended with sludge-biochar at three levels: 0 (control), 1% and 2% of its dry weight, and packed into plastic buckets (9.45-L) to a bulk density of 1.1 g cm-3, each treatment had three replicates. Winter wheat (Triticum aestivum L.) was grown in the greenhouse. Afterwards, spinach (Spinacia oleracea), and Mung bean (Vigna radiata) were sequentially grown under field conditions (each crop cycle lasted for three months). The above-ground biomass was collected and oven-dried at 65°C for 72 hours to assess the plant biomass yield. Soil health parameters such as aggregates stability, pH, electric conductivity (EC), soil respiration, and microbial biomass C were measured. Soils amended with 2% biochar demonstrated higher biomass in winter wheat and spinach compared to 1% biochar and unamended control, on the other hand, mung bean did not present significant differences in all treatments. Similarly, 2% biochar demonstrated high aggregates stability (19.85%) and significant differences compared to control (9%) and 1% biochar (8.3%). Soil pH was greater in 2% biochar (6.5) compared to control (5.8) and 1% biochar (5.5). EC was in the ideal level (<2.7 dS m-1) for all treatments. Soil respiration rate did not demonstrate significant differences in all treatments. Microbial biomass C was higher in control and 2% biochar with significant differences towards 1% biochar. The presented research outcomes provide additional evidence that converting sewage sludge to biochar is a promising strategy to reuse the waste. Also, 2% sludge-biochar was the ideal application rate to promote plant growth, enhance aggregates stability and reduce soil acidity. However, the effect of sludge biochar amendment was not observed in soil biological properties. Therefore, long-term field experiments are needed to assess the amendment effect of sludge-biochar on microbial biomass C and respiration rate to validate the persistent efficacy of sludge-biochar amendments on facilitating crop production, soil biological properties, and overall soil health.